Organizing for impact: International organizations and global pension policy. (April 2019) - Heneghan, Martin; Orenstein, Mitchell A
The internal dynamics and politics of international organizations influence how international policy agendas are set and how effectively they are pursued. International organizations are open systems which respond and adapt to the external policy environment in order to remain relevant to global policymaking. Through an analysis of the internal politics of the World Bank and International Labour Organization, the leading global agenda-setters for pension reform, this article shows that internal political battles and restructuring have a decisive influence on global pensions policy. Appointment of key personnel and internal reorganization can help make certain policy ideas prominent over others. Scholars should pay greater attention to processes of change within international organizations in order to better understand the international agenda setting process.